2018
DOI: 10.1007/s00705-018-3974-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of chikungunya viruses isolated during the 2015-2017 outbreaks in different states of India, based on their E1 and E2 genes

Abstract: During 2015-2017, chikungunya virus (CHIKV) showed a resurgence in several parts of India with Karnataka, Maharashtra and New Delhi accounting for a majority of the cases. E2-E1 gene based characterization revealed Indian subcontinent sublineage strains possessing Aedes aegypti mosquito-adaptive mutations E1: K211E and E2:V264A, with the 211 site positively selected. Novel mutational sites E1: K16E/Q, E1: K132Q/T, E1: S355T, E2: C19R and E2:S185Y could be associated with epitopes or virulence determining domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…A short distance away in Salvador, Brazil, two vertically infected infants developed a rash, fever, and signs of bacterial infection but recovered within a month after delivery, even though one of the infants had developed a grade 1 intracerebral hemorrhage [83]. In 2016, a new E1: K211E mutation was identified in India, Bangladesh, and Brazil through phylogenetic studies (Table 1) [55,95]. It was shown that the E1: K211E mutation correlated with enhanced viral transmission in Ae.…”
Section: Chikv In Neonates and Children After Global Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…A short distance away in Salvador, Brazil, two vertically infected infants developed a rash, fever, and signs of bacterial infection but recovered within a month after delivery, even though one of the infants had developed a grade 1 intracerebral hemorrhage [83]. In 2016, a new E1: K211E mutation was identified in India, Bangladesh, and Brazil through phylogenetic studies (Table 1) [55,95]. It was shown that the E1: K211E mutation correlated with enhanced viral transmission in Ae.…”
Section: Chikv In Neonates and Children After Global Expansionmentioning
confidence: 99%
“…It was shown that the E1: K211E mutation correlated with enhanced viral transmission in Ae. aegypti though studies linking this mutation with human disease have not been published [55]. Furthermore, published alignments show that many other mutations are present in these outbreak isolates.…”
Section: Chikv In Neonates and Children After Global Expansionmentioning
confidence: 99%
“…During the 2006 outbreak, 27 districts including Gulbarga, Tumkur, Bidar, Bellary, Chitradurga, Davangere, Kolar, and Bijapur reported a large number of cases in Karnataka accounting for 762 026 suspected cases reported in India . Even though there had been a marked fall in CHIKV cases in the state in 2007 and 2010, Karnataka and Maharashtra together accounted for nearly 63.1% of the 62 268 cases in the year 2017 . In this context, we decided to estimate the seroprevalence of CHIKV in South Karnataka.…”
Section: Introductionmentioning
confidence: 99%
“…CHIKV has been classified into three distinct genotypes: Asia; East/Central/South African (ECSA) and West African9. CHIK isolates identified in India during 1963, and 1973 belonged to Asian genotype; however, recent epidemics in Indian Ocean and Indian subcontinent were caused by virus of the Indian Ocean Lineage (IOL)9 which has emerged from ECSA genotype. The appearance of new genotypes of ECSA strains was resulted due to microevolutionary changes in the CHIKV genome10.…”
mentioning
confidence: 99%
“…Full genome sequencing and phylogenetic analysis of CHIKV isolate were performed using MEGA5.1 ( https://mega.software.informer.com/5.1 ) with the neighbour-joining method9. Comparative amino acid analysis was also performed using the CHIKV prototype (S27 East-Central South African) strain from Africa and the Karnataka 2006 strains (IOL group).…”
mentioning
confidence: 99%